Users' assessment on interior environment of a hospital outpatient unit in Malaysia / Zanariah Abu Samah, Norhati Ibrahim and Mohd Hanif Abd Wahab - Ibrahim, Norhati; Abd Wahab, Mohd Hanif; Abu Samah, Zanariah (Faculty of Architecture, Planning and Surveying, 2013)
Assessment on the physical design of healthcare facilities from the perspective of the patient and their family members (user) is the method to understand their expectation, preferences and experiences. This paper reports the study conducted on an outpatient unit in Malaysia, focusing particularly on the interior design characteristics. The study adopted post occupancy evaluation technique that combines baseline analysis, occupancy survey and walkthrough observation methods. The study findings indicate that the case study, which has served the public for more than 20 years, is performing moderately on all interior design aspects. Users' assessments did not score any of the facility "good" in terms of their interior quality, suggesting the desire for improvement to the current facility.